Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.



Simplify the given expression:

(−5 + 3i) • (1 − 2i)



Sagot :

[tex] (-5 + 3i) (1- 2i)=\\ -5+10i+3i+6=\\ 1+13i[/tex]
[tex](-5+3i)\cdot(1-2i)\\\\=-5+10i+3i-6i^2\\\\=-5+13i-6(-1)\\\\=-5+13i+6\\\\=\boxed{1+13i}[/tex]


[tex]i=\sqrt{-1}\to i^2=-1[/tex]